ANALISA STRUKTUR PASAR DAN EFISIENSI INDUSTRI PERBANKAN DI INDONESIA PERIODE 2017-2012 - Nuraini Chaniago (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2014)
The purpose of this study was to determine how the market structure and efficiency of banking industry in Indonesia.The analysis technique used in this research is to use the concentration ratio (CR20) and the Herfindahl Hirchman Index (HHI), and DEA (Data Envelopment Analysis). This study uses data on the number of banking and corporate assets to determine the efficiency of using the 20 banks in the Input and Output of the report Indonesian banking in the period 2007-2012. The results showed the level of concentration ratio (CR20) range from 77.69% - 79.47%. The figure shows the structure of the banking industry 2007-2012 period was a tight oligopoly. which means that the structure of the banking industry in Indonesia is not structured oligopoly monopoly but because it is not close to 1. When viewed competition banks in Indonesia is competitive with high concentration and competitive, it is characterized by competition between the market share of twenty dominant company in the Indonesian banking industry in the number of assets. In the calculation of the twenty study Indonesian banking industry in the period 2007-2012 by using the method of DEA (Data Envelopment Analysis) produced differences in the efficiency of each bank, Of the twenty 20 Indonesian banking industry that has not reached the maximum level of efficiency that is 100% should refer to the banking has reached a maximum level of 100% in accordance with the characteristics of banking itself.